High-Performance Liquid Chromatography Method for Determination of Diltiazem in Human Plasma - Baviskar, Dheeraj; Sharma, Rajesh; Jain, Dinesh (Asian Journal of Chemistry, 2010)
A simple rapid, selective sensitive and novel high pressure liquid chromatographic method was developed and validated for the assay of diltiazem. Sample preparation was performed by liquid-liquid extraction in t-butyl methyl ether. The organic solvent was evaporated and the residue dissolved in a mobile phase. Aliquots of 20 μL were injected automatically into the chromatograph. The separation of diltiazem was achieved on a reversed phase (C18) column with a mobile phase consisting of 10 mM ammonium acetate:acetonitrile (55:45 v/v). Quantitation of diltiazem was performed by UV detection at 239 nm. The linearity range was 20 to 640 ng/mL. Inter-day and intra-day accuracy and precision was found 90.44-109.34, 3.74-3.80 and 99.89-103.71, 7.00-10.15, respectively. Long term stability for 30 days of diltiazem in human plasma was proved as per guidelines.